Coverage Expansions and Utilization of Physician Care: Evidence From the 2014 Affordable Care Act and 1966 Medicare/Medicaid Expansions - Gaffney, Adam (Am J Public Health, 2019)
Objectives. To evaluate the effects of the 2 major coverage expansions in US history—Medicare/Medicaid in 1966 and the Affordable Care Act (ACA) in 2014—on the utilization of physician care. Methods. Using the National Health Interview Survey (1963–1969; 2011–2016), we analyzed trends in utilization of physician services society-wide and by targeted subgroups. Results. Following Medicare/Medicaid’s implementation, society-wide utilization remained unchanged. While visits by low-income persons increased 6.2% (P < .01) and surgical procedures among the elderly increased 14.7% (P < .01), decreases among nontargeted groups offset these increases. After the ACA, society-wide utilization again remained unchanged. Increased utilization among targeted low-income groups (e.g., a 3.5-percentage-point increase in the proportion of persons earning less than or equal to 138% of the federal poverty level with at least 1 office visit [P < .001]) was offset by small, nonsignificant reductions among the nontargeted population. Conclusions. Past coverage expansions in the United States have redistributed physician care, but have not increased society-wide utilization in the short term, possibly because of the limited supply of physicians. Public Health Implications. These findings suggest that future expansions may not cause unaffordable surges in utilization.